Waste : a handbook for management - Letcher, T. M. (Trevor M.); Vallero, Daniel A. (Burlington, MA : Academic Press, 2011)
'Preface Waste: A Handbook of Waste Management is designed to be a resource for the designer, practitioner, researcher, teacher and student. Waste is one of those entities which is defined by everyone, but not truly and completely understood by anyone. The scientist, engineer and consumer each define waste correctly, yet differently. The overriding challenge for the authors was to provide some uniformity, yet allow for the diversity of the various aspects of waste in this handbook. After all, a handbook is often the beginning of the search for information, certainly not the end. We have borrowed from all scientific disciplines, and a few humanities, to arrive at a balanced resource. And, indeed, balance is the key to environmental science and engineering'--
Includes bibliographical references and index.
Keywords: Factory and trade waste -- Handbooks, manuals, etc; Refuse and refuse disposal -- Handbooks, manuals, etc